Duodenal ulcer double jeopardy: a case report of sequential bleeding and perforation - Tabassum, Azra; Ali, Summiaya; Selvendran , Selwyn (International Surgery Journal, 2025)
We reported a rare case of a 78-year-old woman who presented with acute duodenal ulcer bleeding requiring emergency surgical intervention. Despite initial control of the bleeding, she subsequently developed a new duodenal ulcer perforation, which necessitated prompt reoperation. This case highlights the importance of timely surgical intervention and meticulous clinical decision-making in managing complex gastrointestinal emergencies in an acute surgical setting.